2017
DOI: 10.1093/hmg/ddx285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of shared genetic aetiology between osteoarthritis and bone mineral density identifies SMAD3 as a novel osteoarthritis risk locus

Abstract: Osteoarthritis (OA) is a common complex disease with high public health burden and no curative therapy. High bone mineral density (BMD) is associated with an increased risk of developing OA, suggesting a shared underlying biology. Here, we performed the first systematic overlap analysis of OA and BMD on a genome wide scale. We used summary statistics from the GEFOS consortium for lumbar spine (n = 31,800) and femoral neck (n = 32,961) BMD, and from the arcOGEN consortium for three OA phenotypes (hip, ncases=3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 63 publications
1
41
0
4
Order By: Relevance
“…We obtained genome-wide summary data for T2D from the DIAGRAMv3 meta-analysis 17 , and for SCZ from the Psychiatric Genomics Consortium (PGC) meta-analysis 19 . To assess the genetic overlap between the two data sets, we performed three complementary analyses, which have been described previously 37 and are briefly outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained genome-wide summary data for T2D from the DIAGRAMv3 meta-analysis 17 , and for SCZ from the Psychiatric Genomics Consortium (PGC) meta-analysis 19 . To assess the genetic overlap between the two data sets, we performed three complementary analyses, which have been described previously 37 and are briefly outlined below.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the observed genetic correlations are also consistent with the genetic pleiotropy and shared pathways among skeletal phenotypes. In supporting this notion, several individual OA associated SNPs were associated with height or BMD (Reynard and Loughlin, 2013 ; Hackinger et al, 2017 ), and OA and LDD were found to share some common genetic risk factors (Song et al, 2008 ; Williams et al, 2011 ). At single SNP level, we also replicated the recent finding of Bjornsdottir et al ( 2017 ) and showed that the height-increasing allele SNP rs6651255 was associated with the increase of two LDD scores in the HKDD cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Of the nine identified variants in the primary analysis, several were associated with the minimum joint space width phenotype, but only a nominal association between an intergenic variant rs116882138 and centre-edge angle (a feature of DDH, β = − 1.1388, P = 0.03), and no association with alpha angle (a feature of cam morphology), was found. Tachmazidou et al [125], in the largest GWAS of OA published to date, including 77,052 cases and 378,169 controls in a meta-analysis examining 17.5million variants, identified 64 signals (52 novel) at MAF > 0.01 on top of 34 previously established loci [124,126,128,[130][131][132][133][134][135][136][137][138][139][140][141][142]. Pathways analysis using MAGMA, PASCAL, and DEPICT Although associations with other demographic characteristics and disease states were examined by linkage disequilibrium regression analysis using LDHub [91], specific direct associations with joint shape were not explored.…”
Section: Evidence From Oa Susceptibility Studiesmentioning
confidence: 99%